2013
DOI: 10.1186/1471-2407-13-409
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density in birth cohorts of Danish women: a longitudinal study

Abstract: BackgroundBreast cancer is the leading malignant disease among western women with incidence increasing over time. High mammographic density is a well-established risk factor for breast cancer. We explored trends in mammographic density across birth cohorts to gain further insight into possible time trends in women’s mammographic density that might explain the historical increase in breast cancer incidence.MethodsData derived from two mammography screening programs in Denmark from 1991 to 2001, including on ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…We detected a strong effect of birth cohort on MD, finding that younger cohorts of women (born in 1945 to 49) had significantly higher MD than women from the oldest cohorts (1930 to 1934), in agreement with Hellman et al . [43]. Our study expands on evidence provided by Harris et al .…”
Section: Discussionsupporting
confidence: 88%
“…We detected a strong effect of birth cohort on MD, finding that younger cohorts of women (born in 1945 to 49) had significantly higher MD than women from the oldest cohorts (1930 to 1934), in agreement with Hellman et al . [43]. Our study expands on evidence provided by Harris et al .…”
Section: Discussionsupporting
confidence: 88%
“…Users of hormone therapy have a higher mammographic density than nonusers . The possible birth cohort effect on mammographic density observed in the earlier Danish study was seen for both users and nonusers of hormone therapy, but the density levels were considerably higher in the user than in the nonuser group . The Dutch data analyzed in our study were derived from September 2003 to September 2016.…”
Section: Discussionmentioning
confidence: 60%
“…In a recent pooled analysis, the effect of aging and menopausal status on mammographic density was investigated, and the authors found density to decrease with increasing age, and to be lower in postmenopausal than in premenopausal women of the same age. A Danish study with repeated measurements for the same women over a 10‐year period indicated a birth cohort effect on density with an increase in the proportion of women with mixed/dense mammographic density from women born in the 1920s to women born in the 1940s.…”
Section: Introductionmentioning
confidence: 99%
“…During the early screening period from 1991–2001, one- or two-view mammograms were taken and mammographic density assessed by highly trained radiologists. Mammographic density refers to the regions of non-radiolucent, or bright, portions of the radiographic image of the breast, and represents the relative proportion of fibroglandular to fatty tissue ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…High mammographic density is one of the strongest known risk factors for breast cancer ( 7 , 8 ), associated with a four- to six-fold increased risk of breast cancer when comparing women with high density in more than 75% of the breast to those with less than 5% mammographic density ( 4 ). Additional risk factors for breast cancer include the female gender, genetic inheritance, age, country of birth, parity, body mass index (BMI), age at onset of menarche and menopause, and hormone replacement therapy (HRT) ( 5 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%